2017
DOI: 10.1210/jc.2017-00448
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-Induced Thyroiditis: Comprehensive Clinical Review and Insights Into Underlying Involved Mechanisms

Abstract: Thyroid dysfunction is common in cancer patients treated with pembrolizumab. Reversible destructive thyroiditis and overt hypothyroidism are the most common clinical presentations. The mechanism of thyroid destruction appears independent of thyroid autoantibodies and may include T cell, NK cell, and/or monocyte-mediated pathways. Because the thyroid is a frequent target of anti-PD-1 therapies, patients with therapeutically refractory thyroid cancer may be ideal candidates for this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
237
4
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(292 citation statements)
references
References 60 publications
16
237
4
12
Order By: Relevance
“…To get a better understanding of the development of the thyroid dysfunction after treatment with ipilimumab [52, 55], pembrolizumab [48, 49, 51, 56] or nivolumab [57, 58], investigators measured serum levels of thyroid stimulating hormone (TSH), free thyroxine (FT 4 ), and/or triiodothyronine (T 3 ) at baseline and during the treatment, as well as thyroperoxidase and thyroglobulin antibodies [48, 49, 51]. For example, Osorio et al reported that 10 of 48 (21%) patients who were euthyroid at baseline developed hypothyroidism during pembrolizumab treatment requiring thyroid hormone replacement.…”
Section: Thyroid Dysfunctions Following Administration Of Monoclonalmentioning
confidence: 99%
“…To get a better understanding of the development of the thyroid dysfunction after treatment with ipilimumab [52, 55], pembrolizumab [48, 49, 51, 56] or nivolumab [57, 58], investigators measured serum levels of thyroid stimulating hormone (TSH), free thyroxine (FT 4 ), and/or triiodothyronine (T 3 ) at baseline and during the treatment, as well as thyroperoxidase and thyroglobulin antibodies [48, 49, 51]. For example, Osorio et al reported that 10 of 48 (21%) patients who were euthyroid at baseline developed hypothyroidism during pembrolizumab treatment requiring thyroid hormone replacement.…”
Section: Thyroid Dysfunctions Following Administration Of Monoclonalmentioning
confidence: 99%
“…According to the literature, while thyrotoxicosis could be transient, all patients developing hypothyroidism should usually continue hormone replacement therapy throughout the observation period, as hypothyroidism is likely to be permanent …”
Section: Discussionmentioning
confidence: 99%
“…Delivanis et al reported recovery of pembrolizumab-induced thyroiditis in 4/7 (57%) patients. 33 It is noteworthy that two cases with hyperthyroidism who required high-dose systemic corticosteroids for the management of other immunerelated toxicities did not become hypothyroid. 31 The authors assumed that immunosuppressive therapy may prevent the development of hypothyroidism in those with ICIs-related thyroiditis.…”
mentioning
confidence: 98%
“…The authors noticed an increased number of circulating CD56+CD16+ NK cells and an elevated surface expression of HLA-DR in the inflammatory intermediate CD14+CD16+ monocytes and assumed that this may explain the destruction of the thyroid. 33 The onset of thyroid disease usually occurs after 2-4 cycles of therapy. Aggravation of existing autoimmunity has been reported; [33][34][35] however, whether individual genetic susceptibility plays a role has not yet been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation